1994
DOI: 10.2214/ajr.162.2.8310928
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patellar tracking in patients with suspected patellar malalignment: cine MR imaging vs arthroscopy.

Abstract: OBJECTIVE.The CONCLUSION.We conclude that motion-triggered cine MR imaging of active extension of the knee enables the dynamic evaluation of patellar bracing and is therefore suitable for noninvasive analysis of patellar tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…Logic would suggest there is a difference; science has yet to examine it. As McNally et al 56 7 demonstrated significant correlation between what they termed a "semi-quantitative" arthroscopic assessment of patellar tracking and patellar tracking as measured by non-weight-bearing dynamic MRI films. However, the semiquantitative assessment was itself solely based upon the arthroscopist's subjective impression of normal patellar tracking.…”
Section: Gold Standardmentioning
confidence: 99%
See 4 more Smart Citations
“…Logic would suggest there is a difference; science has yet to examine it. As McNally et al 56 7 demonstrated significant correlation between what they termed a "semi-quantitative" arthroscopic assessment of patellar tracking and patellar tracking as measured by non-weight-bearing dynamic MRI films. However, the semiquantitative assessment was itself solely based upon the arthroscopist's subjective impression of normal patellar tracking.…”
Section: Gold Standardmentioning
confidence: 99%
“…2,35 Other studies on the measurement of patellar alignment have restricted their subjects to only those with clinically proven subluxation/dislocation. 7,37,58,71 In contrast, when authors have differentiated between PFPS and patellar subluxation/dislocation, they have reported large and significant differences in patellar alignment between these 2 diagnostic groups, 1,28,50 as well as no difference between individuals with PFPS versus asymptomatic patellae. 92 Other definitions of patient populations for patellofemoral measurement studies include clinical subsets, such as "anterior knee pain resistant to conservative treatment," 56 and groups with a vague and unspecified collection of signs and symptoms, such as "suspicion of patellofemoral pain/malalignment, requiring tracking studies" 62 or "symptoms of pain or instability."…”
Section: Arthroscopicmentioning
confidence: 99%
See 3 more Smart Citations